Effect of the position of the PCM on the thermal behavior of a multilayer wall of a building in summer period - Lajimi, Nour; Boukadida, Noureddine (Frontiers in Environmental Science, 2023)
In Tunisia, this sector will occupy the first place in terms of energy consumption in a few years. To remedy this, we must move towards renewable energy sources that partially or totally replace fossil fuels such as oil, coal, etc., and developing ways to make the building more energy efficient in order to save and reduce energy consumption while working to ensure better comfort for the occupant. This work deals with a numerical study based on the nodal method using software (DIGITAL Visual FORTRAN95) to predict the effect of integrating a PCM layer on the thermal behavior of a two-zone building. The effect of the location of the PCM in the wall on its thermal behavior is demonstrated, and the thermal performance of the PCM is demonstrated by considering energy indicators based on the indoor air temperature and the indoor and outdoor surface temperature of the building. It was concluded that the incorporation of PCM into the building envelope increased its thermal inertia, directly influencing the perception of thermal comfort. This indicates that the use of PCM can contribute to improved thermal performance and a more comfortable indoor environment.